2021
DOI: 10.3389/fcell.2021.799772
|View full text |Cite
|
Sign up to set email alerts
|

BMP Signaling: Lighting up the Way for Embryonic Dorsoventral Patterning

Abstract: One of the most significant events during early embryonic development is the establishment of a basic embryonic body plan, which is defined by anteroposterior, dorsoventral (DV), and left-right axes. It is well-known that the morphogen gradient created by BMP signaling activity is crucial for DV axis patterning across a diverse set of vertebrates. The regulation of BMP signaling during DV patterning has been strongly conserved across evolution. This is a remarkable regulatory and evolutionary feat, as the BMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 147 publications
(320 reference statements)
0
11
0
Order By: Relevance
“…66 They have crucial roles during embryogenesis, mainly in mesoderm formation, cardiac and bone development. 67,68 Later on, they were found to be a ubiquitous molecule which plays a vital role in almost all organ systems, and are involved in cellular growth, apoptosis and differentiation of specialized cells within the intestinal epithelium. 69,70 BMP signaling pathway is initiated when BMP ligands bind to the transmembrane tyrosine kinase receptors BMP type II receptors (BMPRII), which then recruits and phosphorylates BMP type I receptors (BMPRI).…”
Section: Regulating Intestinal Epithelial Cell Fatementioning
confidence: 99%
See 1 more Smart Citation
“…66 They have crucial roles during embryogenesis, mainly in mesoderm formation, cardiac and bone development. 67,68 Later on, they were found to be a ubiquitous molecule which plays a vital role in almost all organ systems, and are involved in cellular growth, apoptosis and differentiation of specialized cells within the intestinal epithelium. 69,70 BMP signaling pathway is initiated when BMP ligands bind to the transmembrane tyrosine kinase receptors BMP type II receptors (BMPRII), which then recruits and phosphorylates BMP type I receptors (BMPRI).…”
Section: Regulating Intestinal Epithelial Cell Fatementioning
confidence: 99%
“…BMP ligands are members of the transforming growth factor‐β (TGF‐β) signaling family 66 . They have crucial roles during embryogenesis, mainly in mesoderm formation, cardiac and bone development 67,68 . Later on, they were found to be a ubiquitous molecule which plays a vital role in almost all organ systems, and are involved in cellular growth, apoptosis and differentiation of specialized cells within the intestinal epithelium 69,70 …”
Section: Regulating Intestinal Epithelial Cell Fatementioning
confidence: 99%
“…BMP signaling exhibits pleiotropic effects on the developing nervous system and adult homeostasis. The BMP signaling gradient establishes the dorsoventral axis and negatively regulates neural induction to suppress neuroectoderm formation ([ 9 , 10 ], reviewed in [ 11 ]). Once the neural tube closes, BMP functions as a morphogen to regulate neural tube patterning and specify the neuronal subtypes in the dorsal neural tube (reviewed in [ 12 ]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the detailed molecular mechanism has not been fully elucidated; therefore, we investigated the functional role of Gsc in activating chrd transcription. In contrast, Bmp signaling is predominant in the ventral region of the early gastrula embryo, promoting ectodermal differentiation [ 10 , 11 ]. We reported that Bmp signaling activates the expression of Ventx1.1 (a homeobox transcription factor [TF]) [ 12 ] to repress the expression of organizer and neural target genes [ 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%